Some epidemiological features and effects on reproductive performance of endemic porcine parvovirus infection - Too, H. L.; Love, R. J. (Wiley, 1986)
The time of development of demonstrable antibody to porcine parvovirus (PPV) was determined for 661 gilts entering the breeding herd in a 2800 sow intensive piggery; 13.2% of these gilts did not have detectable antibody to PPV when first introduced into the breeding herd at 25 to 26 weeks of age. Exposure to PPV was found to vary in different sheds and even in different areas within a shed. Gilts that developed antibody to PPV during the first third of pregnancy were not adversely affected. Those that developed antibody during the middle third of pregnancy had fewer piglets born alive, more stillborn piglets and more mummified foetuses.